Dampak Sistem Keuangan Desa (Siskuesdes) Terhadap Transformasi Digital dalam meningkatkan Pelayanan Publik Pengelolaan Keuangan Desa - Lenny Marliani; Wahib Assyahri (Jurnal Ilmu Sosial dan Humaniora, 2024)
The Village Financial System (Siskeudes) is designed to manage village finances efficiently and transparently, facilitating digital recording, reporting, and management of village funds in village financial management in Bengkayang Regency. The problem in this study is the impact of the role of the Siskeudes application in improving the performance of public services in Bengkayang villages. This study aims to analyze the impact of Digital Transformation in improving Siskeudes Public Services in village financial management in Bengkayang Regency. The method used in this research is descriptive qualitative method with data collection techniques using observation, interviews and document studies. The results of this study indicate from 5 indicators that: (1) Relative Advantage: Village staff recognize the efficiency and transparency provided by Siskeudes in budget management. (2) Complexity: Technical challenges, such as staff understanding and skills, affect the complexity of using Siskeudes. (3) Compatibility: The compatibility of Siskeudes with village administration tasks influences adoption. (4) Trialability: Training and technical support assisted staff in piloting and overcoming technical obstacles that occurred. (5) Observability: Financial transparency through Siskeudes allows communities to see the benefits.